P-154 Gbch assessment and coordination team – developing a new model of referral management and care coordination. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Heaps, Kate; Lundy, Jane; McCarthy, Ali; Rattigan, Carla; Sevant, Debbie; Smyth, Sue; Tumelty, Ellen
Abstract : As the Hospice hasdeveloped from a small inpatient/day care service to an organisation with a broad range of end of life/specialist palliative care services across a broad range of settings, a number of referral mechanisms and entry points developed and despite attempts to integrate services as much as possible, the system was flawed. The new Hospice Assessment and Coordination Team was set up to address these issues; making decisions based on the most appropriate level of service for each person's needs, reducing delays and duplication and providing clarity about responsibilities and roles in care coordination and allocation of resource to meet demand. ACT is a new central point to manage referrals, capacity and demand and care coordination; the service takes account of emerging strategy around funding and contracting models and simplifies access for patients, carers and referrers. It aims to enablegreater emphasis on case finding and care coordination in thelocal population andbetter utilisation of generalist services, enabling specialist care to be available when it is needed. ACT provides a consistent and flexibleresponse around the clock, promoting better cross-team working and ensuring efficient and effective use of stretched resources to meet growing demand. Referrals are processed using clearprotocols with specified response times and KPIs, each referral is triaged according to urgency, level of need and preferences. Following initial triage and/or assessment, the patient is booked into a service and where appropriate, an initial care plan is negotiated. Hospice ACT maintains an up to date record of availability of all services, planned admissions and discharges which is visible by the whole clinical and management team. In addition to management of referrals, ACT coordinates care for less complex or more stable patients who are on the EPaCCS register, under the care of generalists. Implementation of the model, early service data and the staffing model will be presented.